Molecular identification of Giardia duodenalis isolates from Fars province, Iran - Rayani, Mohammad; Unyah, Ngah Zasmy; Hatam, Gholamreza (Tehran University of Medical Sciences Publications, 2014)
Background Giardia duodenalis is one of the most common human intestinal protozoan parasites worldwide and is endemic throughout the world with a vast range of mammalian hosts. The present study aimed to identify the prevalence of G. duodenalis isolates and determine the most common of its assemblages in the patients referring to health centers and hospitals in Fars province, Iran that will be subjected to further molecular investigation. Methods We collected 1000 human fecal samples from health centers and hospitals in Shiraz, Iran in a one year period from September 2009 to August 2010. Microscopic examination for the presence of G. duodenalis cysts and trophozoites was performed by direct wet mount before and after the concentration techniques. Extraction of DNA was performed by Phenol-Chloroform-Isoamylalcohol (PCI). G. duodenalis-positive specimens were analyzed by PCR. A fragment of the SSU-rDNA (292 bp) gene was amplified by PCR using the forward primer RH11 and the reverse primer RH4. Genotyping was performed using sequence analysis of G. duodenalis glutamate dehydrogenase gene using primers GDHeF, GDHiF, and GDHiR. Results The prevalence of Giardia infection was 10.7% (107/1000) examined based on microscopic examination. PCR identified 80% (40/50) of the samples as positive for G. duodenalis based on SSU-rDNA amplification on sucrose gradient samples. Besides, genotyping results indicated 32 isolates (80%) as assemblage AII and 8 isolates (20%) as assemblage BIII and BIV based on the DNA sequence analysis of the glutamate dehydrogenase locus of G. duodenalis. Conclusion The findings of this study emphasize that Iran (Fars Province) is a favorable area for giardiasis with an anthroponotic infection route.